Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1993
DOI: 10.1136/ard.52.8.613
|View full text |Cite
|
Sign up to set email alerts
|

Renal effects of aspirin and low dose methotrexate in rheumatoid arthritis.

Abstract: Objectives-The aim of this investigation was to study the glomerular and tubular effects of low doses (15 mg) of methotrexate in patients with rheumatoid arthritis with and without combined treatment with aspirin (2 g single dose). Methods-Renal function was measured by the plasma clearance of EDTA labelled with chromium-51 (51Cr-EDTA) and mercaptoacetyltriglycine labelled with technetium-99 m (9'Tc-MAG-3). Results-Clearance of 5tCr-EDTA was reduced from 98 (6) to 87 (5) ml/min (mean (SEM)) for patients receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
3

Year Published

1996
1996
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 8 publications
3
36
0
3
Order By: Relevance
“…For ibuprofen and naproxen, studies showed conflicting results [33][34][35] . Four studies evaluating high-dose ASA (1.3-4.5 g/day) reported an increase of serum concentration of MTX [45][46][47][48] (Level of evidence 4).…”
Section: Resultsmentioning
confidence: 99%
“…For ibuprofen and naproxen, studies showed conflicting results [33][34][35] . Four studies evaluating high-dose ASA (1.3-4.5 g/day) reported an increase of serum concentration of MTX [45][46][47][48] (Level of evidence 4).…”
Section: Resultsmentioning
confidence: 99%
“…Low dose, which was thought to be safe to the kidney, has been shown to be nephrotoxic in patients with rheumatoid arthritis. Glomerular function and tubular function are reported to be altered after low-dose MTX therapy in patients with rheumatoid arthritis [16,17] . The potential toxicity of high-dose MTX can be prevented by vigorous hydration and alkalinization of the patient.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, plasma clearance studies [12] indi cated that low-dose MTX can indeed provoke significant nephrotoxicity in man involving tubules and glomeruli.…”
Section: Discussionmentioning
confidence: 94%
“…Miescher et al [11] also stated that no unequivocal signs of renal toxicity could be detected in kidney biopsy specimens after prolonged treatment with MTX. However, the recent clearance studies of Seideman et al [12] showed significant renal effects in man follow ing treatment with low-dose MTX.…”
Section: Introductionmentioning
confidence: 99%